Efektivitas Terapi Aktivitas Kelompok Stimulasi Persepsi Halusinasi terhadap Penurunan Kecemasan Klian Halusinasi Pendengaran di Ruang Sakura RSUD BANYUMAS - Isnaeni, Januarti; Wijayanti, Rahayu; Upoyo, Arif Setyo (Jurnal Keperawatan Soedirman, 2008)
Schizophrenia is a common health problem in around the world, around 70% of people suffering from schizophrenia experience hallucination. Auditory hallucination’s client feel that they can hear the voices without source of sound. That situation will cause toward anxiety level patient. One of the nursing interventions that nurses do to the auditory hallucination’s client is that making group activity therapy of perception stimulation of hallucination. The aim of study was to find out the affectivity group activity therapy of perception stimulation of hallucination in decrease auditory hallucination’s client at Sakura ward RSUD Banyumas. This research used comparative with quasi experimental design: non equivalent control group design. The samples used purposive sampling with 30 auditory hallucination’s client as respondents. Data analyzed was using distribution of frequency and paired t test. Based on paired t test show that t value at: 6,859 with p value 0,000 which was smaller than alpha: 0,05 which mean that the research hypothesis was received. Group activity therapy of perception stimulation of hallucination was influenced with decrease of auditory hallucination’s client anxiety at RSUD Banyumas.